Generalizations of some fractional integral inequalities for m-convex functions via generalized Mittag-Leffler function - FARID, Ghulam; ABBAS, Ghulam (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this paper we are interested to present some general fractional integral inequalities for m-convex functions by involving generalized Mittag-Leffler function. In particular we produce inequalities for several kinds of fractional integrals. Also these inequalities have some connections with known integral inequalities. Mathematics Subject Classification (2010): 26A51, 26A33, 33E12.